Legal Protection for Children Victims of Physical Bullying Reviewed from the Victimological Aspect - Sinaga, Hotman; Zulyadi, Rizkan; Pinem, Serimin (Journal La Sociale, 2025)
Physical bullying of children is a social problem that has a wide impact, both physically, psychologically, and socially. From a victimology perspective, children as victims of physical bullying have the right to receive protection and recovery to reduce the negative impacts experienced. This study examines the victimology component in order to assess legal protection for kids who are physically bullied. The study employs a normative legal approach, analyzing relevant laws and regulations and examining case studies of their application. The study's findings suggest that Law Number 35 of 2014 concerning Child Protection provides legal protection for kids who are physically bullied. However, in practice, there are still various obstacles, such as low public awareness of victims' rights, lack of psychological and social assistance, and obstacles in the law enforcement process. From a victimology perspective, recovery efforts for victims should not only focus on the legal aspect, but also include psychological rehabilitation, social assistance, and family support so that victims can recover optimally. This study recommends the need for synergy between law enforcement officers, child protection agencies, and the community in ensuring protection and recovery for victims of physical bullying. In addition, there needs to be strengthening of policies related to victim assistance and increasing public awareness to create a safer environment for children.